The Influence Of Work Environment And Work Culture On Employee Spirit Of Maybank Finance Regional Sumatra With Motivation As An Intervening Variable - Rahmadi, Muhammad; Zunaidah, Zunaidah; Widiyanti, Marlina; Perizade, Badia; Karimudin, Yos (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the direct effect of work environment and work culture on morale, the indirect effect of work environment and work culture on morale through Maybank Finance Sumatra Regional employees' work motivation as an intervening variable. Respondents in this study were taken using a census. The total population for filling out the questionnaire is 159 respondents. The data analysis technique used is the Structural Equation Model (SEM). The results of this study indicate that work environment and work culture have an effect on motivation, work motivation has a positive effect on morale, work motivation and work culture have a positive effect on morale, work environment has a positive influence on morale through motivation as an intervening variable, work culture has has a positive effect on the morale of Maybank Finance Regional Sumatra through work motivation as an intervening variable. This proves that work motivation is an intervening variable or a good intermediary variable for the influence of the work environment on morale. A comfortable and conducive work environment can influence employees to be more motivated in improving the quality and quantity of their performance to be more effective and efficient.